Análise do poder de compra do salário mínimo a partir da alteração do processo de correção do salário estabelecido em 2007 - Welter, Yasmin Ertel (Universidade do Vale do Rio dos Sinos, 2021)
Since the beginning of the social organization of work, the minimum wage has played an important role in the lives of workers, seeking to ensure that they receive a decent remuneration for their labor. In Brazil, this value is annually readjusted and, in 2007, it was proposed that this readjustment should be based on a mathematical formula composed of the Gross Domestic Product and the inflation index measured by the National Consumer Price Index, obtaining thus real gains above the general increase in prices. This study aims to understand the behavior of the minimum wage after implementing this rule, comparing its evolution to the different levels of inflation measured in Brazil and evaluating its efficiency according to the new variables added to its readjustment. Through this study, it was observed that the minimum wage presented real gains when applying the Gross Domestic Product as a variable of increase to inflation, however it was also observed that after economic crises where the variation of the Gross Domestic Product was negative, there was no significant increase above the inflation in the minimum wage gains for workers.
Keywords: Salário Mínimo; Reajuste; Inflação; Produto Interno Bruto; Minimum wage; Readjustment; Inflation; Gross Domestic Product